RAGA MUSIC AND EMOTIONAL BALANCE: A PSYCHOLOGICAL AND LITERATURE-BASED STUDY - Joshi, Amogh; Kaslikar, Pravin (ShodhGyan-NU: Journal of Literature and Culture Studies, 2026)
Indian classical music is deeply rooted in the concept of raga, which represents a structured melodic framework capable of evoking specific emotional states. In the Indian aesthetic tradition, music is not merely an artistic expression but also a medium for influencing human emotions and psychological well-being. Contemporary research in psychology and neuroscience has also confirmed that music has a profound effect on emotional regulation and cognitive processes. The present study examines the relationship between Indian raga music and emotional balance from psychological and literature-based perspectives. The study primarily relies on analytical and interpretative examination of existing literature in the fields of music psychology, neuroscience, Indian musicology, and music therapy. Scholarly works of researchers such as Patel, Koelsch, Juslin, Sloboda, and Thaut have been analyzed to understand how musical structures influence emotional responses. The findings suggest that raga music has the ability to influence emotional states through its unique melodic patterns, tonal hierarchy, and expressive characteristics. Neuroscientific research indicates that music activates the limbic system of the brain, which is associated with emotional processing and affective responses. As a result, listening to or performing raga music can reduce psychological stress, enhance emotional stability, and promote positive mental states. The study concludes that Indian raga music can function as a powerful tool for achieving emotional balance and psychological well-being. Therefore, its applications can be extended to areas such as music therapy, mental health promotion, and emotional education.